Akkermansia muciniphila participates in the host protection against helminth-induced cardiac fibrosis via TLR2. - Jiaqi Wang; Xiaolei Liu; Ruohang Sun; Hanhai Mao; Mingyuan Liu; Xuemin Jin (PLoS Pathogens, 2023)
Helminth Trichinella spiralis (Ts) is one of the major pathogens of human infective myocarditis that can lead to cardiac fibrosis (CF). The gut microbiota involved in this pathology are of interest. Here, we use mice infected with Ts as a model to examine the interactions between gut microbes and host protection to CF. Infected mice show enhanced CF severity. We find that antibiotics treatment to deplete the microbiota aggravates the disease phenotype. Attempts to restore microbiota using fecal microbiota transplantation ameliorates helminth-induced CF. 16S rRNA gene sequencing and metagenomics sequencing reveal a higher abundance of Akkermansia muciniphila in gut microbiomes of Ts-infected mice. Oral supplementation with alive or pasteurized A. muciniphila improves CF via TLR2. This work represents a substantial advance toward our understanding of causative rather than correlative relationships between the gut microbiota and CF.